GRAMMATICAL ERRORS IN STUDENTS’ WRITING: DESCRIPTIVE STUDY ON GRADE 7 STUDENTS - Indri Ayu Lestari; Juliansyah - Juliansyah; Yoga Pratama (Universitas Bunda Mulia, 2020)
Grammatical error is difficult to be avoided by every learner. Grade 7 students in class observed are smart enough. Yet, they frequently make grammatical errors in the sentences when they write essay. Because of that, analyzing the errors in writing is one of appropriate ways to know student’s ability. In this research, the researchers ask the students to make descriptive text or essay. There are 7 titles of essay that each student can choose. There are only 7 texts that the researchers analyze in which each text represents different title of text. To analyze the texts, the researchers use Corder’s theory which focuses on 4 types of error, namely: (1) Error of Omission, (2) Error of Selection, (3) Error of Addition, and (4) Error of Ordering. The highest percentage of error is Error of omission that takes 45.28%. Error of Selection, Error of Addition, and Error or Ordering follow with 33.96%, 18.87%, and 1.88%. Based on the analysis, the reasons of why the students make errors are: (1) the students do not master grammar in detail, (2) the students forget the grammar rules though they have learnt it, and (3) the students have limited vocabularies. Further studies need to be conducted for more detail findings.